Optimalisasi Zakat Produktif Berupa Pemberdayaan Peternak Ayam Kampung di Dusun Semenok Desa Ngebel - Amalia, Naluri Sari; Rifai, Ahmad Maufiq; Agustin, Lia; Utomo, M. Bagas Adi Ilham; Ihsan, M. Nur; Prihamayu, Amrul Hinung (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2024)
The study aims to analyze an empowerment community project carried out as a productive zakat program conducted in Semenok Hamlet, Ngebel Village, Ponorogo Regency. The main program is about native chicken farming for the villagers. This study is using a qualitative approach. Primary data was collected from the program’s beneficiaries through interviews and secondary data was sourced from books, electronic media, or scientific journals relevant to productive zakat implementation. This program is specifically focused on one of the eight asnaf categories, that is, the poor community in that hamlet. The program was carried out by distributing 3 native chickens along with their feed to 17 beneficiaries of the program (zakat recipients). This zakat is expected to be their initial capital in hopes the poor could be more prosperous. This program hopefully could provide financial assistance for the beneficiaries so they could transform into a muzakki in the future. Penelitian ini bertujuan untuk menganalisis optimalisasi program pemberdayaan zakat produktif untuk peternakan ayam kampung di Dusun Semenok, Desa Ngebel, Kabupaten Ponorogo. Metode penelitian ini adalah metode kualitatif. Sumber data penelitian ini adalah hasil wawancara kepada mustahik penerima zakat dan literatur ilmiah yang membahas tentang pemberdayaan masyarakat, baik berupa buku, media elektronik, maupun jurnal yang relevan. Program pemberdayaan zakat produktif ini disalurkan kepada salah satu dari golongan 8 asnaf, yaitu masyarakat miskin. Program dilaksanakan dalam bentuk pemberian ayam kampung sebanyak 3 ekor beserta pakan ayam. Bantuan tersebut diharapkan dapat menjadi modal awal masyarakat penerima bantuan sehingga para mustahik dapat berkembang menjadi lebih sejahtera. Mustahik penerima bantuan ini berjumlah 17 orang. Dengan adannya program ini, diharapkan mustahik dapat terbantu dari segi ekonomi sehingga kelak dapat bertransformasi menjadi muzakki.